Aplikasi Penyewaan Perlengkapan Studio Foto (Kamera dan Aksesoris) Berbasis Web di Cinema Kreatif Desain Pekanbaru - Yulisman Yulisman (Program Studi Teknik Informatika Universitas Pamulang, 2019)
Cinema Kreatif Design Pekanbaru is a business entity in the field of camera rental services and photo studio equipment. The existing rental system is not yet effective, even though it already uses computers in processing data, but only uses Microsoft office applications, such as Microsoft Excel and Microsoft Word and companies experience obstacles in managing and processing data that is increasingly increasing. Errors in recording camera data and photo studio equipment that are rented and returned. This study aims to help companies provide information to customers or tenants about the specifications of cameras and photo studio equipment that they want to rent online by building a camera rental application and web-based photo studio equipment at the Cinema Kreatif Design Pekanbaru. The method used in making the application is the waterfall method, and the data collection techniques used by researchers are observation, interviews and literature. As a tool of analysis and design used is UML (Unified Modeling Language). The programming language used is PHP (Hypertext Preprocessor) and MySQL database. The results of the study can be concluded that with the application of camera rental and photo studio equipment, it is expected to help employees of Cinema Kreatif Design Pekanbaru in managing tool data, customer data, member data, rentals, returns and can reduce errors in the process of recording data and reduce errors in manufacturing report.